DEGRADAÇÃO SISTÊMICA DO TRABALHO NO AGROHIDRONEGÓCIO - Thomaz Junior, Antonio (Universidade Federal do Ceará, 2017)
ABSTRACT We have used the concept of hydro-agricultural business in our studies, since we understand that capital, when searching for flat, fertile lands with favorable logistics, also requires water availability and expropriates traditional and native peasant populations. Thus, whether superficial or from aquifers, water is at the center of territorial disputes and conflicts. It is necessary to add, that in this route of exclusion the systemic degradation of workers and of the natural and transformed environments has intensified. That is, the differentiated advantages for the monoculture / latifundial / agricultural-exporting project, which has heavily penalized and condemned millions of workers to exclusion and expulsion from the land, and the population in general to diseases, chronic risks of contamination and pure and simple discarding. These consolidate themselves in the name of the modernization of production processes, as evidenced by the research in which many of us are involved. Learning about these processes and their effects requires care and attention to specific occurrences and procedures to address them. This may be a new phase of social exclusion, in the context of the systemic degradation of labor in hydro-agricultural business.

RESUMEN Hemos utilizado el concepto de agrohidronegócio en nuestros estudios, porque creemos que el capital cuando busca un terreno llano y fértil, con la logística favorables etc., expropia poblaciones originales. Por lo tanto, sea superficial, sea de los acuíferos, el agua está en el centro de las controversias y los conflictos territoriales. Debe agregar a la ruta de exclusión que la degradación sistémica de los trabajadores, los entornos naturales y transformados se han intensificado. Es decir, las distintas ventajas para el proyecto de monocultivo/latifundista/exportación de productos agrícolas, que ha penalizado y condenado a la exclusión millón de trabajadores, a la desterreação, y la población en general a las enfermedades crónicas, los riesgos de contaminación, se consolida en nombre de la quimificação de los procesos de producción modernos, como puede se constata a través de la investigación que muchos de nosotros estamos involucrados. Esto puede ser una nueva fase de la exclusión social en el ambiente de la degradación sistémica del trabajo en agrohidronegócio.

RESUMO Utilizado o conceito de agrohidronegócio nos nossos estudos, por entendermos que o capital, quando busca terras planas, férteis, com logística favorável, também requer disponibilidade hídrica e expropria populações camponesas, tradicionais e originárias. Assim, seja superficial, seja de aquíferos, a água está no centro das disputas e conflitos territoriais. É necessário acrescentar, nessa rota de exclusão, que a degradação sistêmica dos trabalhadores, dos ambientes naturais e transformados tem se intensificado. Isto é, as vantagens diferenciadas para o projeto monocultor/latifundista/agroexportador, que tanto tem penalizado e condenado milhões de trabalhadores à exclusão, à desterreação, e a população em geral, às doenças, aos riscos crônicos das contaminações, ao descarte pura e simplesmente, se consolidam em nome da quimificação dos processos de produção modernos, como se constata por meio das pesquisas em que muitos de nós estamos envolvidos. Apreender esses processos e seus efeitos exigiu cuidados e atenções para com as ocorrências e procedimentos específicos para abordá-las. Essa pode ser uma nova fase da exclusão social, no ambiente da degradação sistêmica do trabalho no agrohidronegócio.
SYSTEMIC DEGRADATION OF WORK IN HYDRO-AGRICULTURAL BUSINESS
DEGRADACION SISTÉMICA DEL TRABAJO EN EL AGROHIDRONEGOCIO
Keywords: Systemic degradation; Labor; Hydro-agricultural business; Working class; Health-disease; Degradação sistêmica; Trabalho. Agrohidronegócio; Classe trabalhadora; Saúde-Doença